THE RISKS OF A GLOBAL SOCIETY: MOVING TO A NEW METHODOLOGICAL PARADIGM - T. V. Naumova (Научный вестник МГТУ ГА, 2016)
The historical stages of reflection of the risk phenomenon are identified. The peculiarities of formation of the global world as a risk stage of social development, constructive and at the same time destructive, producing the good and disasters are considered.